Ethnomedicinal Plants Used against Dental Diseases in Asansol Raniganj Coalfield Area of West Bengal - Saha, Amit (Indian Forester, 2017)
An ethnobotanical study was conducted to document the ethnomedicinal plants used against dental problems by tribals and people of other castes of Asansol Raniganj coalfield area. In this study many plants were reported to cure various dental diseases and for the maintenance of proper oral health and hygiene.